The Influence of Teachers’ Leadership and Motivation on Social Science Learning Outcomes MA Yahisha Cihampelas Bandung - Trihastuti, Meiwatizal; Latief, Suryawahyuni; Kholid, Mohammad Ridho (Bulletin of Science Education, 2021)
- The aim of this study was to know the influence of teachers’ leadership and motivation, to know the learning outcomes on learning social science. This research was quantitative with regression linear. The researchers taken 30 students from class XI IPS (social science) 1 Year 2020/2021 at MA Yahisha Cihampelas Bandung. The result show that the hypothesis in this study can be accepted, namely there is an influence of Teachers' Leadership and Motivation on the Social Science Learning Outcomes of Class XI IPS 1 Students 2020/2021 at MA Yahisha Cihampelas Bandung. With a high level of significance. In other words, Teachers' Leadership and motivation can be used as a method to improve student learning outcomes, in this case, Social Science lessons in the teaching and learning process. Keywords: Teachers’ Leadership, Social Science Learning Outcome, Motivation